Um estudo sobre a distribuição das transferências condicionais no setor de saúde no Brasil - Simão, Juliana Barby (2013)
This paper empirically studies some determinants of the intergovernmental transfers in the Brazilian health care sector. In particular, we discuss and investigate the existence of a positive relationship between municipal revenues and federal transfers received through Unified Health System (Sistema Único de Saúde – SUS) by municipalities. As SUS legislation associates mandatory spending in health of municipalities to a portion of its revenues, the phenomenon was also investigated in the light of the flypaper effect theory. The empirical analysis was based on the estimation of fixed effect panel models. We considered a panel of Brazilian municipalities from 2002 to 2010. Data was mostly obtained from Departamento de Informações do SUS (DATASUS) and Sistema de Informações sobre Orçamentos Públicos em Saúde (SIOPS), both from Ministry of Health of Brazil. Our results show that municipal tax revenue has indeed a positive and significant impact on receiving transfers. Considering the redistributive aspect, this relation may not be desirable. We argue about the possibility that the funds transferred by SUS are not sufficient, so that a financial compensation of the local governments would be required to cover programs and services in their entirety. We also identified some evidence that there may be political factors influencing receipt of funds from SUS.